TEKNOLOGI KOMUNIKASI 3G DARI SUDUT PANDANG COMPUTER MEDIATED COMMUNICATION - Joanne Tjahyana, Lady (Institute of Research and Community Outreach - Petra Christian University, 2007)
The emergence of technological innovation of 3G-Communication had resulted in impacts and reforms in communication paradigm. The 3G was implemented on Smart Phone that represented a joint between computer technology and cellular telephone. In line with computer functions on communication media of cellular telephone%2C would also lead to issues of Computer Mediated Communication (CMC) on application of smart phone for communication; particularly 3G that provided facilities and services%2C that increasingly added and sustained communication functions through computer media into smart phone. Through this article%2C the writer wanted to discuss application of 3G-communication technology from standpoint of CMC. Particularly related to issues of CMC%2C among others were Digital Divide%2C Antisocial Behavior%2C and Online Ethics. Abstract in Bahasa Indonesia : communication technology%2C 3g%2C computer mediated communication